PENERAPAN E-GOVERNMENT TERHADAP KETERBUKAAN KEUANGAN PEMERINTAHAN DESA - sahala purba (Worksheet : Jurnal Akuntansi, 2026)
This study aims to determine the effect of the Implementation of E-Government on the Financial Transparency of Village Government in Alasa District, North Nias Regency.. This study is quantitative in nature and uses primary data. The population in this study consists of all village officials in the villages of Alasa Subdistrict, with a sample of 71 respondents selected using purposive sampling. The data analysis technique used in this study was descriptive statistics. The researcher tested the quality of the primary data by conducting validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests using SPSS 26. The results of this study indicate that the implementation of e-government has a positive and significant effect on the transparency of village administration. The implications of this study indicate that optimizing the implementation of digital systems in village administration can increase public information disclosure and strengthen the transparency of village administration management.